Management of inoperable carcinoma of the breast by curative radiotherapy and chemo-hormonotherapy - Petera, J; Filip, S; Slampa, P; Soumarová, R; Coupek, P; Zatloukal, P (Onkologie, 2001)
BACKGROUND: The aim of this study was to evaluate local control and its relation to survival in patients with locally advanced breast cancer treated with curative irradiation and systemic therapy. PATIENTS AND METHODS: 240 patients with unresectable breast cancer were treated with curative radio- and chemo- or hormonotherapy from 1990-1995. The frequency of distant dissemination and the overall survival of patients with and without complete local control were compared. RESULTS: Complete local control was achieved in 63% of patients. Complete local control correlated with decrease of distant metastases and increase of survival in comparison with patients without complete local control. CONCLUSION: Radiotherapy without surgery provides insufficient local control in patients with locally advanced breast cancer. Complete local control is an important factor for prevention of distant dissemination and for survival.
Keywords: senioři; Carcinoma, Ductal, Breast; Doxorubicin; methotrexát; Breast Neoplasms; cyklofosfamid; senioři nad 80 let; adjuvantní radioterapie; Radiography; fluoruracil; Fluorouracil; Cisplatin; Middle Aged; cisplatina; míra přežití; Adult; kombinovaná terapie; Follow-Up Studies; následné studie; Aged, 80 and over; duktální karcinom prsu; Neoplasm Staging; doxorubicin; ženské pohlaví; radiografie; Cyclophosphamide; Humans; Methotrexate; Survival Rate; lidé středního věku; Antineoplastic Agents, Hormonal; Antineoplastic Combined Chemotherapy Protocols; nádory prsu; Combined Modality Therapy; staging nádorů; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Radiotherapy, Adjuvant; lidé; hormonální protinádorové látky